2018
DOI: 10.1002/micr.30322
|View full text |Cite
|
Sign up to set email alerts
|

Obliquely‐arranged double skin paddles: A novel design to reconstruct extensive head and neck defects with a single fibula or peroneal flap

Abstract: With the design of obliquely-arranged double paddles, we may maximize the harvested skin area of lateral lower leg to reconstruct an extensive head and neck defect with a single free flap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…20 Other advantages associated with the ALT include a large, customizable skin paddle, the presence of multiple perforators, an opportunity for vascularized nerve transfer (as shown in two patients in our series), and a more acceptable donor site morbidity than with the RFA. 21 Despite technical concerns that have been voiced by the surgical community with the transfer of two free flaps, we did not observe significantly increased total flap or skin paddle loss complication rates when compared with patient outcomes with single flap transfers. We evaluated the transfer of 55 free flaps with a total of three total flap losses, yielding a total flap success rate of 95%.…”
Section: Discussioncontrasting
confidence: 59%
“…20 Other advantages associated with the ALT include a large, customizable skin paddle, the presence of multiple perforators, an opportunity for vascularized nerve transfer (as shown in two patients in our series), and a more acceptable donor site morbidity than with the RFA. 21 Despite technical concerns that have been voiced by the surgical community with the transfer of two free flaps, we did not observe significantly increased total flap or skin paddle loss complication rates when compared with patient outcomes with single flap transfers. We evaluated the transfer of 55 free flaps with a total of three total flap losses, yielding a total flap success rate of 95%.…”
Section: Discussioncontrasting
confidence: 59%
“…3 The chimeric fibula free flap with double skin paddles later became an option. [6][7][8][9][10] Studies on perforator anatomy by Jones et al and Yu et al showed the traditional distal skin paddle to be extremely reliable with up to 3 septocutaneous perforators. 4,5 A proximal musculocutaneous perforator was present in 67%-84% of cases that could supply the proximal skin paddle.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Anatomical studies of perforator anatomy have found a common musculocutaneous perforator that can supply a separate, proximal skin paddle in the fibula free flap, which has expanded its reconstructive uses. [4][5][6][7][8][9][10] We present the reconstruction of a complicated and extensive mandibulofacial defect using one of the largest reported fibula free flaps.…”
Section: Introductionmentioning
confidence: 99%
“…The osteocutaneous fibular flap, described first by Hidalgo in 1989 for mandibular reconstruction (Hidalgo, 1989), underwent continued evolution of flap design to improve its soft‐tissue characteristics. Several modifications have been developed, for instance providing a second skin island using three different techniques: a central de‐epithelialized skin paddle (Deleyiannis et al, 2008; Jones et al, 2003; Yadav et al, 2012), a distally‐based double‐skin paddle (DSP) (Kubo et al, 2013; Lin et al, 2019; Maciejewski et al, 2008; Yang et al, 2000), or a proximally and distally‐based DSP (Chang & Yu, 2017; Cheng et al, 2009; Kannan et al, 2013; Leclère et al, 2014; Potter et al, 2014; Roan et al, 2013; Yu et al, 2011) (Figure 1). However, according to the current literature, no optimal reconstructive method has been standardized.…”
Section: Introductionmentioning
confidence: 99%